Human Security: A Strong Foundation for Multilateral Cooperation - Jonathan Granoff (Cadmus, 2022)
Human Security is the conceptual framework through which multilateral cooperation and common security amongst nations, which is now necessary, can be achieved. The article argues that the concept of human security has not reached its potential to catalyse progress yet. Human Security focuses on people-centered and context-specific responses to challenges. Several existential challenges such as a stable climate, healthy oceans, and pandemics cannot be addressed successfully at a national level. Even the SDGs require a human security integrated approach in order to overcome the inefficiency of silos. Change is needed quickly. Human security can help make that change.